KAJIAN KARAKTERISTIK MEKANIK ROLLER COMPACTED CONCRETE (RCC) SEBAGAI BAHAN PERKERASAN JALAN - Sukmawan Hendriyanto (UNIVERSITAS LAMPUNG, 2011)
RCC concrete pavement is concrete pavement that has durability, economic value, long life and low maintenance service life. In this study conducted in the field compaction with baby roller more or less as much as 3-5 times the trajectory, and retrieval of test specimen cubes (10x10x10) and beam (10x10x30), with a concrete cutting tools. Taking a test specimen in the laboratory of conventional concrete cubes (15x15x15). The composition of mixtures used were water: sand: split: cement is 108:811:1217:300 (kg/m3). Variations in the age of treatment (7,14,21 and 28 days), and performed two tests, namely: the testing of compressive strength and lentur.Hasil tensile strength showed that the mixture of the same compressive strength and flexural strength RCC is higher than conventional concrete., more economical, faster utilization after the implementation of the work. Compressive strength obtained at 28 days was 29.25 MPa and 5.14 MPa flexural tensile strength, is still included in the range required by the ACI (American Concrete Institute) that the range of tensile strength for RCC split between 400 (2.75 MPa) and 600 psi (4.13 MPa) at 28 days, for compressive strength are eligible for RCC mixtures where, according to the specifications for RCC of the PCA (Portland Cement Association) where the requirements are between 28 MPa - 69 MPa.